Local Strain Engineering of Two-Dimensional Transition Metal Dichalcogenides Towards Quantum Emitters - Ai, Ruoqi; Cui, Ximin; Li, Yang; Zhuo, Xiaolu (Nano-Micro Letters, 2025)
Two-dimensional transition metal dichalcogenides (2D TMDCs) have received considerable attention in local strain engineering due to their extraordinary mechanical flexibility, electonic structure, and optical properties. The strain-induced out-of-plane deformations in 2D TMDCs lead to diverse excitonic behaviors and versatile modulations in optical properties, paving the way for the development of advanced quantum technologies, flexible optoelectronic materials, and straintronic devices. Research on local strain engineering on 2D TMDCs has been delved into fabrication techniques, electronic state variations, and quantum optical applications. This review begins by summarizing the state-of-the-art methods for introducing local strain into 2D TMDCs, followed by an exploration of the impact of local strain engineering on optical properties. The intriguing phenomena resulting from local strain, such as exciton funnelling and anti-funnelling, are also discussed. We then shift the focus to the application of locally strained 2D TMDCs as quantum emitters, with various strategies outlined for modulating the properties of TMDC-based quantum emitters. Finally, we discuss the remaining questions in this field and provide an outlook on the future of local strain engineering on 2D TMDCs. Highlights: 1 Methods for creating the local deformation in two-dimensional transition metal dichalcogenides (2D TMDCs) are introduced. 2 Modulations of local strain on their optical properties and excitonic behaviors are discussed. 3 Quantum emitters based on strained 2D TMDCs and other applications are presented.